Management Techniques and Behavioral Counseling Procedures in Developing Human Personality - Thessia Permata Bunda; Netrawati; Zadrian Ardi; Rahmad Firmansyah; Pu’ad Maulana (Manajia: Journal of Education and Management, 2024)
Behavioral counseling is one of the counseling approaches used to change individual behavior. This paper aims to describe how behavioral counseling views humans and personality as well as outline the goals, processes and techniques in behavioral counseling. The method used is a literature review by collecting various information from relevant sources regarding behavioral counseling. With behavioral counseling, clients are expected to create new behaviors, eliminate inappropriate behaviors and strengthen and maintain desired behaviors.